Análise da aplicação dos requisitos do selo casa azul em empreendimentos de habitação de interesse social - Leitão, Marisa Teófilo (2013)
The spread of projects based on the principles mentioned above, arose the need to create systems to evaluate the performance of these buildings. Many countries make use of their own environmental certification and, in Brazil, despite recent, there are certification systems for measuring the degree of sustainable construction. The first Brazilian certification to consider the context of the Brazil buildings was the AQUA which is an adaptation of the French environmental certification system to the Brazilian civil construction characteristics. The other Brazilian certification is the Selo Casa Azul released by CAIXA. This seal intends also to comprise the social housing construction (HIS) financed by CAIXA. In this context, this article seeks to analyze the necessary improvements to the Selo Casa Azul for deployment in HIS. To achieve the goal, was initially performed a comparative study of environmental certifications, with subsequent analysis of housing projects in order to verify the level of compliance with the requirements of the Selo Casa Azul. Finally, an interview with the manufacturers of this type of enterprise and CAIXA’s managers. The interview tried to raise the advantages and difficulties of implementation of the Selo Casa Azul.In conclusion it was seen that the requirements of Selo Casa Azul has a small deficiency in relation to other labels already used in the country. It was also identified the low attendance of HIS seal requirements in question, as well as identified the lack of knowledge of both the builders when the residents and the low value paid by cash to finance housing projects, which hinders the deployment of the requirements. As proposed improvement is the inclusion of new requirements to the seal. We also suggest a revision of the amounts paid by CAIXA to enterprises for HIS well as a greater incentive for builders are interested in joining the stamp. It is highlighted as a improvement proposal an awareness work post-occupation of the residents.